Fungal community associated with mixed infection of anthracnose and stem end rot diseases in Chokanan Mango - ANI WIDIASTUTI; SURYANTI SURYANTI; ALVINA CLARA GIOVANNI; ISLAMINATI ANNA SANTIKA; NIKEN RASMI PARAMITA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Widiastuti A, Suryanti, Giovanni AC, Santika IA, Paramita NR. 2023. Fungal community associated with mixed infection of anthracnose and stem end rot diseases in Chokanan Mango. Biodiversitas 24: 2163-2170. Anthracnose and stem end rot are the top two prevalent diseases causing losses in mango fruit worldwide. Both diseases often appear together in ripened fruits. The aim of this research was to evaluate the fungal community associated with mixed infection of anthracnose and stem end rot diseases in Chokanan mango based on metagenomics analysis through amplicon targeted next generation sequencing. The results showed that approximately 152,000 sequences were observed. The average total tags from the observed OTUs number were 146,485, of which 126,230 were taxon tags. The ten most common occurring fungal genera were Colletotrichum, Penicillium, Diaporhte, Purpureocillium, Aspergillus, Cunninghamella, Neofusicoccum, Mortierella, Rhizopus, and Kazachstania. Of these, genus Colletotrichum showed 77% dominance of based on Krona display value. Based on the number of OTUs, seven species, such as Colletotrichum gloeosporioides (Penz.) Penz. & Sacc., Penicillium simplicissimum (Oudem.) Thom, Neofusicoccum cordaticola Pavlic, Slippers & M.J.Wingf., Diaporthe arengae R.R.Gomes, Glienke & Crous, Purpureocillium lilacinum (Thom) Luangsa-ard, Houbraken, Hywel-Jones & Samson, Alternaria alternata (Fr.) Keissl., and Fusarium oxysporum Schltdl., showed dominance in mixed infection. These findings reveal the major status of post-harvest pathogens in mango fruits that should be controlled. This is the first report on N. cordaticola and D. arengae associated with mixed infection of anthracnose and stem and rot disease on post-harvest mango in Indonesia.